Immediate effects of photobiomodulation with low-level laser therapy on muscle performance: an integrative literature review - Vanessa Mouffron Novaes Alves; Renata Maria Moreira Moraes Furlan; Andréa Rodrigues Motta (Revista CEFAC, 2019)
ABSTRACT Purpose: to analyze the influence of low-level laser on muscle performance and to identify the most used dosimetric parameters. Methods: the search for articles was carried out on the PubMed, BVS, Web of Science and SciELO platforms. The articles selected were original ones, with available abstracts and that evaluated the use of photobiomodulation on muscular performance. The data were analyzed according to the author, year of publication, sample, place of application, parameters evaluated, wavelength, dosimetry used and results found. Results: the final sample consisted of 27 articles published between 2008 and 2017. The sample size in the studies ranged from 8 to 60 individuals, aged from 17 to 70 years. A greater use of infrared wavelength, with punctual applications carried out in the path of the muscle, was observed. Regarding the dose, there was a variation from 0.24 to 50 joules per point. Of the total, only 5 (18.5%) studies had not found significant answers for the considered variables. Conclusion: most of the studies pointed out that low-level laser can improve muscle performance. The methodology used in the work was diversified, rendering data compilation difficult, being impossible to set the ideal parameters for this purpose.